Constant creation in grammatical evolution. (26th April 2007) - Dempsey, Ian; O'Neill, Michael; Brabazon, Anthony
We present an investigation into constant creation in Grammatical Evolution (GE), a form of grammar-based Genetic Programming (GP). The methods for constant creation evaluated include digit Concatenation (Cat) and a grammatical version of ephemeral random constants called persistent random constants. Experiments conducted on a diverse range of benchmark problems uncover clear advantages for a digit Cat approach.